Tailoring Polymeric Nanoparticles as Nanocarriers via RAFT Polymerization - Agustina, Sri (World Chemical Engineering Journal, 2021)
Polymeric nanoparticles are really promising to be used as drug carriers, due to its ability to increase the aqueous solubility of drugs. Polymeric nanoparticles can regulate the drug activity by passive or active targeting to different tissues. RAFT polymerization has become the most approvable technique to synthesize polymeric nanocarriers for drug delivery. By using different RAFT agents, wide ranges of polymeric nanoparticles with various architecture and water solubility can be obtained under mild conditions.